Does Profitability, Firm Size, and Intellectual Capital Affect Firm Value? - Dewi Kurnia Sari; Sigit Hermawan; Hadiah Fitriyah; Nurasik Nurasik (Jurnal Riset Akuntansi Terpadu, 2022)
The purpose of this study is to determine the effect of profitability, company size and intellectual capital on firm value. This type of research is a quantitative research. Researchers use secondary data and data collection using the documentation method. The population of this study are pharmaceutical companies from 2016 to 2021. The sampling technique is purposive sampling and the sample of this research are 10 companies. Different from previous studies using SPSS and eviews, this study uses partial least squares (PLS) to analyze data. Based on the results of this study, it proves that profitability, company size and intellectual capital have an effect on firm value. This means that there is an increase in profitability, company size and intellectual capital can affect a value in the company. Companies can use the results of this research to develop strategies that can increase the value of the company.